Facing time in ischemic stroke: an alternative hypothesis for collateral failure - Pham, Mirko; Bendszus, Martin (Clinical neuroradiology, 2016)
Several randomized-controlled trials could recently demonstrate that ischemic stroke which is caused by large-cerebral-artery-occlusion can be treated effectively by endovascular recanalization. Among these studies, particularly the data from the ESCAPE study further corroborated the strong association between macrovascular pial collateral flow (before recanalization) and clinical outcome after recanalization. This review briefly gives an overview on these data and on the clinical key observations demonstrating this association in practice. Since the ischemic penumbra can only be sustained by collateral flow, the collapse of collateral blood flow or poor collateral filling, observed for example by DSA or CTA before recanalization, seems to be a primary cause of rapidly progressive infarction and futile therapeutic recanalization. However, it needs to be emphasized that the true cause-effect relationship between collateral failure and rapidly progressive infarction of the penumbra, i.e. the high probability of unfavorable clinical outcome despite recanalization, remains unclear. Along this line, an alternative hypothesis is offered viewing the collapse of collateral flow not as a cause but possibly as an inevitable secondary consequence of increasing peripheral/microvascular resistance during progressive infarction.